Carbon nanowalls in field emission cathodes - Belyanin, А.F.; Borisov, V.V.; Daghetsyan, S.A.; Evlashin, S.A.; Pilevsky, A.A.; Samorodov, V.A. (Технология и конструирование в электронной аппаратуре, 2017)
The carbon nanowall (CNW) layers were grown from a gas mixture of hydrogen and methane, activated by a DC glow discharge, on Si substrates (Si/CNW layered structure). The second layer of CNW was grown either on the first layer (Si/CNW/CNW structure) or on Ni or NiO films deposited on the first CNW layer (Si/CNW/Ni/CNW and Si/CNW/NiO/CNW structures). The composition and structure of the resulting layered structures were studied using scanning electron microscopy, Raman spectroscopy, and X-ray diffractometry. It was found that annealing of Si/CNW structure in vacuum, growing of the second CNW layer on Si/CNW, as well as deposition of Ni or NiO films prior to the growing of the second CNW layer improve functional properties of field emission cathodes based on the electron-emitting CNW layers.